INFLUENCE OF Morinda citrifolia, L. FRUIT EXTRACT AS ADJUVANT ON IG-Y PRODUCTION RAISED IN LAYING CHICKENS AGAINST AVIAN INFLUENZA VACCINE - Ediati Sasmito; Sri Harimurti; Hendy Nurhidayat; Wahyu Anggoro; Elika Nur Hikmawati; Joko Tri Wibowo; Atut Sulma Avi; Nurul Hilmi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Immunized avian with vaccine, produces specific antibody in the serum as well as in the egg yolk. An adjuvant is used to augment the effects of a vaccine by stimulating the immune response. Morinda citrifolia, L., especially the fruit contains of some chemical compounds such as polysaccharide, scopoletin, damnacanthal, proxeronine and proxeroninase. All those of active compounds, are soluble in different solvents and have different activities. Some of those compounds have adjuvant activity. The aim of our study was to observe the capability of M.citrifolia fruit extracts as adjuvant to enhance the specific antibody (IgY) production in immunized laying chickens Lohmann strain (28 weeks old) with a commercially available avian influenza (H5N2) vaccine. To the groups (@6) of laying chickens were orally administered once a day, through out of the study, with n-hexane (group I; divided ino 3 sub groups), ethanolic (group II; divided into 3 subgroups) and aqueous extract (group III; divided into 3 subgroups) of M.citrifolia (prepared in capsules) on dose of 29 mg; 58 mg; and 116 mg/chicken/day, respectively, and group IV as plasebo control and group V as normal control. All of the groups were induced with avian influenza vaccine, except the normal control. Eggs of 3, 6, and 10 weeks after immunized, were collected. Isolation of IgY was performed by repeated polyethylene glycol 6000 precipitation steps. IgY obtained was analyzed by indirect ELISA method. The serum was tested for antibody specificity against the influenza H5N2 virus by hemagglutination-inhibition (HI) method. The result of this study showed that the dose of 58 mg/chicken/day of aqueous extract of M.citrifolia fruit had an optimal capability to enhance specific antibody (IgY) as well as IgG serum production against avian influenza (H5N2) vaccine .Key words: Adjuvant, extract, Morinda citrifolia, L., H5N2 vaccine, immunoglobulin yolk (IgY)